Hamstring injuries, from the clinic to the field: A narrative review discussing exercise transfer - Vicens-Bordas, J.; Parvaneh Sarand, A.; Beato, M.; Buhmann, R. (International Journal of Sports Physiology and Performance, 2024)
Purpose The optimal approach to hamstring training is heavily debated. Eccentric exercises reduce injury risk; however, it is argued that these exercises transfer poorly to improved hamstring function during sprinting. Some argue that other exercises, such as isometric exercises, result in better transfer to running gait and should be used when training to improve performance and reduce injury risk. Given the performance requirements of the hamstrings during the terminal swing phase, where they are exposed to high strain, exercises should aim to improve the torque production during this phase. This should improve the hamstrings` ability to resist overlengthening consequently, improving performance and limiting strain injury. Most hamstring training studies fail to assess running kinematics postintervention. Of the limited evidence available, only eccentric exercises demonstrate changes in swing-phase kinematics following training. Studies of other exercise modalities investigate effects on markers of performance and injury risk but do not investigate changes in running kinematics.